Stochastic Speech Understanding for Human-Computer Dialogue - Bohus, Dan (Romanian Journal of Information Science and Technology, 2001)
The thesis describes a domain and language independent semantic analyzer for spoken dialog systems built using a stochastic approach based on Hidden Markov Models and the case grammar formalism.